Increased x-ray attenuation in malignant vs. benign mediastinal nodes in an orthotopic model of lung cancer - Flechsig, Paul; Choyke, Peter; Kratochwil, Clemens; Warth, Arne; Antoch, Gerald; Holland-Letz, Tim; Rath, Daniel; Eichwald, Viktoria; Huber, Peter E.; Kauczor, Hans-Ulrich; Haberkorn, Uwe; Giesel, Frederik L. (Diagnostic and interventional radiology, 2016)
PURPOSE - Staging of lung cancer is typically performed with fluorodeoxyglucose-positron emission tomography-computed tomography (FDG-PET/CT); however, false positive PET scans can occur due to inflammatory disease. The CT scan is used for anatomic registration and attenuation correction. Herein, we evaluated x-ray attenuation (XRA) within nodes on CT and correlated this with the presence of malignancy in an orthotopic lung cancer model in rats. - - METHODS - 1×106 NCI-H460 cells were injected transthoracically in six National Institutes of Health nude rats and six animals served as controls. After two weeks, animals were sacrificed; lymph nodes were extracted and scanned with a micro-CT to determine their XRA prior to histologic analysis. - - RESULTS - Median CT density in malignant lymph nodes (n=20) was significantly higher than benign lymph nodes (n=12; P = 0.018). Short-axis diameter of metastatic lymph nodes was significantly different than benign nodes (3.4 mm vs. 2.4 mm; P = 0.025). Area under the curve for malignancy was higher for density-based lymph node analysis compared with size measurements (0.87 vs. 0.7). - - CONCLUSION - XRA of metastatic mediastinal lymph nodes is significantly higher than benign nodes in this lung cancer model. This suggests that information on nodal density may be useful when used in combination with the results of FDG-PET in determining the likelihood of malignant adenopathy.
Published online 25 November 2015
Gesehen am 02.06.2020